The lapidary elements of the Castle of Belvoir - Anne Flammin; Paul François; Florian Renucci (Medievalista)
The systematic study of the blocks of the Belvoir castle lapidary has allowed us to restore several architectural ensembles that could have belonged to the castle chapel, which has now disappeared. In this article, we present the method of analysis and recording of these blocks, as well as the protocol of 3D reconstruction that allowed us to formulate several hypotheses concerning the shape, decoration and roof of the chapel. One of them proposes an architectural ensemble with an ogival vault, to which numerous lapidary elements seem to belong, but in opposition to the style of contemporary constructions in the Latin East. As for the other, it is based on a style more in line with the architectural context, but few of the stones found could belong to it. Without proposing to definitively settle the question, this article also demonstrates the interest of a very strong interconnection between archaeologists, stone-cutting specialists and architects allowing, around the 3D reconstruction, to propose hypotheses considering all the data of the problem.